BROAD SPECTRUM ANTIMICROBIAL ACTIVITY OF LUMBRICUS RUBELLUS POWDER AGAINST DRUG RESISTANT MICROBES - TRISTIA RINANDA; . SAKDIAH; RISNA OKTAVIA; MEYCHA DA FHONSA; MUFQI FITRA (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Inappropriate uses of antimicrobial drugs have contributed to the development of resistant microbial pathogens. This phenomenon requires discovery and development of potential antimicrobial compounds from organic materials. Lumbricus rubellus is the ubiquitous earthworm containing antimicrobial peptide named Lumbricin-1. The aim of this study was to determine the broad spectrum antimicrobial activity of Lumbricus rubellus powder against several drug resistant microbes such as Multidrug Resistant (MDR) Pseudomonas aeruginosa, Methicillin Resistant Staphylococcus aureus (MRSA) and Fluconazole resistant Candida albicans. This experimental study was conducted using Completely Randomized Design (CRD) with 6 treatment groups consisting of 100 mg, 200 mg, 300 mg, 400 mg and 500 mg L.rubellus powder in 5 ml solvent (acetic acid and acetonitrile) and negative control groups. One percent of each concentration then was used in the antimicrobial activity testing using Kirby Bauer disc diffusion method. Data of this research were analyzed by ANOVA. The results showed that L. rubellus powder in each of the concentrations of 100 mg, 200 mg, 300 mg, 400 mg and 500 mg obtained an average inhibition zone of 14.33 mm, 14.17 mm, 14.00 mm, 15.00 mm and 13.00 mm respectively against MDR P. aeruginosa; 16.75 mm, 18.50 mm, 18.75 mm, 16.75 mm and 17.25 mm against MRSA; 16.50 mm, 18.00 mm, 17.50 mm, 17.75 mm and 16 mm against Fluconazole resistant C. albicans. Statistical analysis revealed that Lumbricus rubellus powder in the tested concentrations showed significant broad spectrum antimicrobial activity against drug resistant microbes (p0.05).